Journey of a standalone paediatric orthopedic day-care surgical center catering wide variety of cases judiciously: a review of 300 surgeries - Paik, Soumya; Bose, Tathagata; Chakrabarty, Koustav; Panda, Chandan (International Journal of Research in Orthopaedics, 2025)
Background: In spite of known advantages of day care surgery (DCS) in children, multiple ambulatory surgical centres (ASCs) in different subspecialities of orthopedics, enhanced recovery after surgery (ERAS) protocol and advancement of paediatric anesthesia with guidelines, we see limited popularity of standalone day care paediatric orthopaedic facilities. We also do not have definite paediatric orthopaedic case guidelines for day care surgery unlike pediatric anesthesia and paediatric surgery. Purpose of this study to determine the possibility of various types of child orthopaedic surgery in a standalone day care set up in a safe, comfortable environment with cost minimisation. Methods: A retrospective review of cases in a standalone private paediatric orthopaedic day care centre involving its first 300 surgeries over a span of two years. Wide variety of paediatric orthopaedic surgeries were performed in spite of having a long exclusion criteria list. Adverse reaction, cost minimisation and comfortable nature of this pathway were assessed. Results: A total of 300 day-care surgeries between 17th August 2023 and 4th July 2025 in our centre. We broadly divided our surgeries into 12 categories like trauma, infection, benign tumour, osteotomy, cerebral palsy, removal of Implant, clubfoot etc. We selected our surgeries after 22 long exclusion criteria. We segregated our surgeries depending on duration of surgery, mode of anaesthesia, bodyweight of patient, age of patients. We had overall 8 adverse events, for an overall 2.6%. Our average surgical cost was USD 564 per surgery. No child suffered psychological disturbances requiring medical intervention. Conclusions: DCS in paediatric orthopaedics in a standalone setup can be performed if we choose our patients judicially and follow appropriate pathways.